Prevalence and risk factors of soil transmitted helminths from rural field practice area of a tertiary care center from northern India - Goel, Shewtank; Tank, Rakesh; Singh, Abhishek; Khichi, Sanjeev Kumar; Goyal, Pooja; Arya, Rakesh (International Journal of Research in Medical Sciences, 2017)
Background: Soil-transmitted helminths (STH) are a major public health problem in our country, affecting the physical growth and cognitive development. STH infections are considered a leading cause of sickness, absenteeism and disability adjusted life years lost. Aim of the study was to assess the prevalence and risk factors of soil transmitted helminths (STH) in Farrukhabad district, India. Methods: A total of 1203 study subjects from 602 eligible households fulfilling the eligibilty criteria. Thus equal number of children and adults were recruited from rural and urban areas. In each household, one child participant of the age 1-15 years and one adult, older than 15 years, and willing to participate, were eligible to participate in this study. All enrolled subjects were provided with a screw- capped plastic container to collect their stool sample. The following day, a field worker visited the subject’s home to collect the container. Saline and iodine wet preparations were examined for the presence of nematode ova. All positive stool samples were re-examined by the McMaster egg counting technique to quantify the number of eggs per gram of stool. Results: Overall prevalence of STH was 14.3% (95% CI 4.4-19.2) among study subjects. Hookworm was the predominant STH identified with a prevalence of 11.3% (95% CI 1.1-17.4), followed by Ascaris lumbricoides with a prevalence of 4.5% (95% CI 0.5-7.6). Prevalence of STH was observed to be 13.2% (95% CI 8.7-17.2) and 7.6% (95% CI 4.4-10.7) in rural and urban areas respectively. Age category, residing in a field-hut, presence of cat at home, presence of untrimmed nails, open air defaecation, habitually eating food that has fallen on the ground, not washing hands with soap and water after defaecation, and consumption of deworming tablet turned out to be independent risk factors for acquiring STH infection in our study. Conclusions: Identification of at-risk groups along with Strategic planning and health education, awareness campaigns along with mass drug administration could reduce the burden of STH significantly.